2020
DOI: 10.7555/jbr.34.20200044
|View full text |Cite
|
Sign up to set email alerts
|

Identification of therapeutic drugs against COVID-19 through computational investigation on drug repurposing and structural modification

Abstract: Global prevalence of coronavirus disease 2019 (COVID-19) calls for an urgent development of anti-viral regime. Compared with the development of new drugs, drug repurposing can significantly reduce the cost, time, and safety risks. Given the fact that coronavirus harnesses spike protein to invade host cells through angiotensin-converting enzyme 2 (ACE2), hence we see if any previous anti-virtual compounds can block spike-ACE2 interaction and inhibit the virus entry. The results of molecular docking and molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Notably, in one of these studies [ 81 ] a better binding activity of tenofovir with the P323L mutated RdRp protein was observed in comparison with remdesivir, further suggesting tenofovir use in COVID-19 treatment. Interestingly, these drugs also seem to bind other crucial viral proteins, such as PLpro and Mpro/3CLpro [ 84 , 85 , 86 ], and to interfere in the interaction between the S protein and ACE2 receptor [ 82 , 83 ], suggesting multiple targets in the virus life cycle for these drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in one of these studies [ 81 ] a better binding activity of tenofovir with the P323L mutated RdRp protein was observed in comparison with remdesivir, further suggesting tenofovir use in COVID-19 treatment. Interestingly, these drugs also seem to bind other crucial viral proteins, such as PLpro and Mpro/3CLpro [ 84 , 85 , 86 ], and to interfere in the interaction between the S protein and ACE2 receptor [ 82 , 83 ], suggesting multiple targets in the virus life cycle for these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies, the spike/ACE2 interaction has been considered the target of simulated inhibition. MD and MDS analyses with 2080 FDA-approved molecules identified 238 compounds virtually binding the spike/ACE2 interaction interface, 10 of which were reported to have antiviral activity and with tenofovir and remdesivir showing the highest docking scores [ 82 ]. The authors found that remdesivir had stronger interactions with ACE2 than with spike, while TDF was closer to and interacted more strongly with the spike protein than the ACE2 receptor.…”
Section: Pre-clinical Studiesmentioning
confidence: 99%
“…Several recent computational studies proposed that some potent molecules either directly bind to the interface, to a distant site from the interface, or to the active site of ACE2 , with the goal of allosterically affecting the interactions between ACE2 and S1 and help prevent the viral entry of SARS-CoV-2. As mentioned earlier, DESRES also shared several MD simulations that were performed for ACE2 in complex with 78 compounds predicted to bind tightly to ACE2 .…”
Section: Resultsmentioning
confidence: 99%
“…The study conducted by salpini et al [45] on several permitted drugs and their metamorphosis effect on the binding affinity for the target enzyme has shown that medicines such as remdesivir display reduction in binding affinity against P323L metamorphosed RdRp; other medicines including tenofovir are found to be responsive against modified enzyme. Yun et al [46] have stated that tenofovir and remdesivir display utmost docking values.…”
Section: Discussionmentioning
confidence: 99%